Age-related characteristics and normative values of F waves in healthy infants. Issue 5 (May 2020) - Pan, Hua; Chen, Na; Lin, Jinxi; Jian, Fan; Zhang, Lei; Wang, Ying; Yang, Shuo; Chen, Lin; Wang, Hengheng; Zhang, Zaiqiang; Guan, Yuzhou; Wang, Yongjun; et al.
Highlights: We established normal values of F waves in infants by evaluating monthly maturational changes. F-wave latencies shorten in the 2nd month of life and change little thereafter during infancy. Testing F waves effectively supplements nerve conduction studies to assess the infants' short limbs. Abstract: Objective: To establish age-related characteristics and normative values of F waves in healthy Chinese infants. Methods: We studied median, ulnar and tibial nerves on one side distally in 229 healthy Chinese infants (108 males) ranging from 1 to 12 months old. Results: Minimal F-wave latencies (Fmin) showed a strong negative correlation to the age for median, ulnar and tibial nerves (P < 0.01) but no correlation to the height. Statistical analyses revealed a significant (P < 0.01) decrease of Fmin during the second month of life and no change (P > 0.05) thereafter. Dividing the infants into 1 month old (Group 1) and 2–12 months old (Group 2), normal values (Mean ± SD ms) of Fmin for tibial, median and ulnar nerves consisted of 23.38 ± 1.68, 17.19 ± 0.95 and 16.47 ± 1.06 for Group 1 and 21.42 ± 1.25, 14.50 ± 1.15 and 14.52 ± 0.90 for Group 2. Conclusion: F-wave latencies shorten in the 2nd month of life and change little thereafter when age-related maturation counters the concomitant growth of the nerve length. Significance: F waves can assess infantile neuropathies as a reliable measure, complementing the technically difficult conventional nerve conduction study in short limbs.